Synthesis and Photoelectric Properties of Donor-Acceptor-Donor Molecule Containing Perylene Diimide - Ming Jiao, Chun; Jun Li, Bing; Li Yi, Si; Xu*, Qing (Asian Journal of Chemistry, 2014)
In this paper, a novel perylene diimide derivative 1,7-bis[N,N-bis(4-phenyl)aniline]perylene diimide (PDI-TPA) was synthesized and characterized by IR spectroscopy, 1H NMR and elemental analysis. Besides, solubility and photoelectric properties of 1,7-bis[N,N-bis(4-phenyl)aniline]perylene diimide were studied. Results show that 1,7-bis[N,N-bis(4-phenyl)aniline]perylene diimide exhibits excellent solubility in common solvents. The absorption bands span a wide range of the visible spectra and optical band gap is 1.68 eV. In addition, 1,7-bis[N,N-bis(4-phenyl)aniline]perylene diimide exhibits an ambipolar behaviour, the highest occupied molecular orbital (HOMO) energy level and the lowest unoccupied molecular orbital (LUMO) energy level are -5.64 eV and -3.94 eV, respectively.